Safety and efficacy of colchicine in crystal-induced arthritis flare in 54 patients with severe chronic kidney disease - Renaud Felten; Bruno Michel; Bénédicte Gourieux; Marion Fourtage; Johanna Bausson; Nicolas Keller; Jean-Jacques Von Hunolstein; Matthieu Sacrez (RMD Open)
Introduction Colchicine, commonly used in gout flare, is contraindicated in severe chronic kidney disease (CKD) (estimated glomerular filtration rate <30 mL/min). However, in this context, there are few alternatives, and colchicine use persists. We evaluated the tolerance of colchicine and its efficacy in patients with severe CKD.Patients and methods All prescriptions of colchicine for managing crystal-induced arthritis flare (gout or calcium pyrophosphate deposition (CPPD) disease) in a hospitalised patient with severe CKD were screened from September 2020 to September 2021. After patient consent and treatment information, clinical and biological safety and efficacy data were prospectively collected from day 1 (D1) to D11.Results We included 54 patients (median age 75 years (IQR 67–83)) with 62 colchicine prescriptions (cases). Twelve (22%) patients were on dialysis. The main reason for hospitalisation was heart failure (31.5%), acute renal failure (22.2%), infection (18.5%) or an acute joint episode (9.3%). In total, 59.3% of patients had diabetes. The prescriptions concerned 58 cases of gout flares, 1 case of CPPD and 3 cases of both. Initial colchicine dosages were ≤0.5 mg/day in 47/62 (75.8%) cases; no dosage exceeded 1 mg/day (median duration of 6 days (IQR 3–11)). Colchicine was well tolerated in 47/61 (77%) cases. No serious adverse event was reported. Colchicine was considered completely effective by the medical team in 48/58 (83%) of cases.Conclusion The use of colchicine, at reduced doses, was mostly effective to treat crystal-induced arthritis flare in 54 patients with severe CKD and was well tolerated, without any serious adverse events.